Primary spinal syringomyelia triggered by a spontaneous spinal cerebrospinal fluid fistula - RANC, Revista Argentina de Neurocirugia; Mezzadri, Juan José; Cragnaz, Ricardo; Lambre, Héctor Eduardo (Revista Argentina de Neurocirugía, 2024)
Background: total or partial obstruction to the circulation of cerebrospinal fluid (CSF) in the spinal canal can cause syringomyelia (SM). One of its causes is spinal CSF fistulas that, by generating intracranial hypotension (ICH) due to excessive fluid drainage, produce tonsillar descent that obstructs CSF circulation. Objectives: to describe and analyze a new case of SM caused by a spinal CSF fistula between the subarachnoid and extradural spaces. Case description: a 44-year-old woman presented with headaches and paresis in both hands. She had undergone surgery twice with a diagnosis of Chiari I: cranio-spinal decompression and duraplasty and then revision of the duraplasty. MRI showed tonsillar descent with syringomyelia and diffuse post-contrast meningeal enhancement. The diagnosis of ICH was made. Myelotomography showed a right radicular cyst at T11-T12 with CSF leakage into the extradural space. Intervention: after analyzing the images, it was decided to address the radicular cyst by injecting 10 cm3 of autologous blood under tomographic control. The control MRI showed an elevation of the cerebellar tonsils and a complete resolution of the syringomyelia, changes that were maintained in subsequent controls. Conclusion: ICH should be considered as a potential cause of syringomyelia associated with tonsillar descent. In this case, treatment of its cause, a type 2a spontaneous CSF fistula, using a targeted blood patch produced reversal of tonsillar descent with resolution of the syringomyelia.